Cinematography, A Medium in International Studies The Germination of a Documentary - Singh, Siddiqa; Gordan-Bates, Dorian; Ziegler, Stefan (Nawi, 2022)
“The Genesis of a Documentary” is the opening article of a trilogy of articles applying research and analysis to a cyclical phenomenon, namely the germination of an idea to a film, to turn it into a cinematographic reality conscious of social impact. This study concerns itself with the position of the researchers and the researched, being part of the former. Retracing the epistemology of an ever-evolving idea, like a kaleidoscope, the article pieces together the memory of key informants to get to the germination of threads of notions, which become a solid reality manifesting itself over time to turn into a cultural expression: a documentary film. Three authors, one article, and voices from the past culminate in a refined picture of the genesis of BROKEN-the-film, an altruistic attempt to continue the implementation of International Law for those whose voices cannot be heard. This article is testimony to the creation of an advocacy tool.